Hydrogen embrittlement of 718 under cathodic polarization. (1st April 2020) - Thodla, Ramgopal; Chandra, Ashwini; Li, Xiaoji; Taylor, Christopher D.; Ke, Huibin; Sridhar, Narasi
Abstract: High strength nickel based alloys are extensively used in both O&G and Navy applications. 718 is one of the most commonly used alloys in these applications. Applied cathodic potential had a significant effect on the crack growth rate (CGR) of various grades of 718. Crevice geometry was used to estimate the crack tip pH and potential conditions under cathodic polarization. Density functional theory (DFT) modelling was performed to estimate the water coverage on fresh metal surfaces of 718 under the crack tip conditions. The CGR was related to the estimated water adsorption on fresh metal surfaces in the measured crack tip conditions.